Method for estimating non-vulnerable remaining battery power based on fractional-order battery model - XIONG NENG; CHEN YIXING; ZHENG MENGQIAN; ZHU QIAO (2018)
The invention discloses a method for estimating non-vulnerable remaining battery power based on a fractional-order battery model. The method comprises the steps that a fractional-order second-order RCmodel is established; model parameters are recognized by using current and voltage response of a battery pack, and nonlinear functions of open circuit voltage and remaining battery power are obtainedby setting current pulse to remain still after discharging is conducted by the current pulse; a Lipschitz condition and a unilateral Lipschitz condition are proposed aiming at non-linear function parts to ensure that positive effects can be achieved by the non-linear functions on the design of an observer; the practicability of the observer is taken into consideration, and bounded gain disturbance is introduced; a linear matrix inequality system is established and solved by ensuring the H infinite performance of an error system to complete the design of the non-vulnerable observer. Accordingto the established fraction